Sistem Informasi Data Karyawan Pada PT. Smart Kebun Adipati Marbau Berbasis Web - Nasution, Hendrik (Journal of Computer Science and Information System(JCoInS), 2022)
PT. Sinar Mas Agro Resources and Technology Tbk, or better known as PT. Smart Tbk, is one of the largest companies that produce consumer goods based on palm oil and also has many branches that are widespread throughout Indonesia, including in the province of North Sumatra. As in North Sumatra regoin PT. Smart has a branch in Padang Halaban, AEK Kuo District, North Labuhanbatu Regency. One of the plantations for PT. Smart Padang Halaban is the Duke's Garden located in the Merbau area of North Labuhanbatu Regency. PT. SMART Tbk kebun Adipati has utilized computer services to support its activities for daily data processing in addition to using Microsoft Word applications also use Microsoft Excel which is standard in data storage. Therefore, the author is very interested to create a processing and storage of employee data that is more attractive, easy to run in data processing, data search, data processing and printing of the data by using a web-based information system. In this designed system also contains employee attendance data entered into the website making it easier for employees to be able to see their own attendance of each employee without ask the attendance data collection officer to print their attendance.